Primary Angioplasty of a Super Dominant Left Anterior Descending Coronary Artery - Dubey, Laxman; Adhikari, Ridhi; KC, Pradip Jung; Panjiyar, Rajesh; Gurung, Tej Bahadur; Subramanyam, Gangapatnam (Journal of College of Medical Sciences-Nepal, 2016)
The posterior descending artery usually arises from either the right coronary artery or the left circumflex artery. Here we report an unusual case of super-dominant left anterior descending coronary artery continuing as the posterior descending artery beyond the crux which was totally occluded in a patient who presented with acute anterior wall myocardial infarction. Successful primary angioplasty and stenting of the super-dominant left anterior descending coronary artery was performed. JCMS Nepal. 2016;12(2):81-82